Learning to forget: Hippocampal–amygdala connectivity partially mediates the effect of sexual trauma severity on verbal recall in older women undiagnosed with posttraumatic stress disorder. Issue 2 (13th February 2022) - McIntosh, Roger; Lobo, Judith D.; Carvalho, Nicole; Ironson, Gail
Abstract: Verbal learning deficits are common among sexually traumatized women who have not been formally diagnosed with posttraumatic stress disorder (PTSD). Aberrant resting‐state functional connectivity (rsFC) of the amygdala and hippocampus are implicated in PTSD and verbal memory impairment. We tested rsFC between bilateral dentate gyrus (DG) and both centromedial (CM) and basolateral (BL) nuclei of the amygdala as statistical mediators for the effect of sexual trauma–related symptom severity on delayed verbal recall performance in 63 older women (age: 60‐85 years) undiagnosed with PTSD. Participant data were drawn from the NKI‐Rockland Study. Individuals completed a 10‐min resting‐state scan, Rey Auditory Verbal Learning Test (RAVLT), and the Sexual Abuse Trauma Index (SATI) from the Trauma Symptom Checklist. Z ‐scores indicating rsFC of DG with BL and CM amygdala seeds were evaluated in two separate mediation models. Higher SATI scores were associated with lower RAVLT after controlling for age, β = −.23, 95% CI [.48, .03], p  = .039. This effect was negated upon adding a negative path from SATI to rsFC of left DG and right CM, β = −.29, 95% CI [−.52, ‐.02], p  = .022, and a positive path from that seed pair to RAVLT List A recall, β = .28, 95% CI [.03, 0.48], p  = .015. Chi‐square fit indices supported partial mediation by this seed pair, p  = .762. In the absence of PTSD sexual trauma symptoms partially relate to verbal learning deficits as a function of aberrant rsFC between left hippocampus DG and right amygdala CM nuclei.